PROFIL BIOAUTOGRAM EKSTRAK FERMENTAT ISOLAT FUNGI ENDOFIT DARI DAUN GALING-GALING (Cayratia trifolia L) SEBAGAI ANTIBAKTERI - Fitriana Fitriana; As Adi Abdullah; Annisa Almagfirah Achmar (As-Syifaa Jurnal Farmasi, 2019)
The research bioautogram profile of fermentate extract endophytic fungi from galing-galing (Cayratia trifolia L) leaf as an antibacterial has been to find the activity of the extract fermentat endophytic fungi isolates against bacterial test using TLC Bioautography. This research begins with the isolation of leaves galing-galing using Potato Dextrose Agar Chloramfenicol (PDAC) media, isolates do purification and macroscopic test. Subsquently isolates were followed by screening endophytic fungi isolates against test bacteria. Isolates that give the most excellent activity followed by fermentation with Maltose Yeast Broth (MYB) media using a shaker speed of 200 rpm at room temperature for 21 days. After the fermented liquid is separated to obtain fermentat and  mycelia. The fermented liquid was then extracted using a liquid-liquid extraction method using ethyl acetate solvents after which it was evaporated with a rotary evaporator until a thick extract was obtained. Extracts obtained followed by TLC Bioautography method using ethyl acetate : n-hexane (4: 1) eluent.  Endophytic fungi were obtained as many as 6 isolates and the best activity was endophytic fungi with IDGG-03 code against test bacteria. The results from the TLC Bioautography profile 2 Bioautography provide active spot with Rf values of 0.09 and 0.54 against the bacteria B. subtilis, V. cholerae and P. aeruginosa.